Legal Politics as a Tool of State Purpose in Making Indonesian Laws Legislation - Fairuz Nabil, Aulia (Yayasan Mentari Madani, 2024)
Indonesia's national legal framework is heavily dependent on legislation. The main way to make laws is through legislation. Due to its coercive and binding legal force, the law is also a very effective tool for legal reform. It is clear that the politics of law is very important for the development of Indonesian legislation, regulations, and the continuity of national law, if you remember that politics An important rule in this process is that the law identifies the principles, structure, and development of the country's legal system. Through this explanatory study with a normative and conceptual approach, the author seeks to restate that lawmakers must adapt to the goals of the state in order to achieve in the production of legitimate goods. So that in making new laws and regulations, always pay attention to the sense of justice, usefulness, and clarity of the law for the community